2016
DOI: 10.1097/gox.0000000000001027
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Alar Nasal Cartilage Defects Using a Tissue Engineering Technique Based on a Combined Use of Autologous Chondrocyte Micrografts and Platelet-rich Plasma: Preliminary Clinical and Instrumental Evaluation

Abstract: Background:Developing cartilage constructs with injectability, appropriate matrix composition, and persistent cartilaginous phenotype remains an enduring challenge in cartilage repair. The combined use of autologous chondrocyte micrografts and platelet-rich plasma (PRP) is an alternative that opens a new era in this field.Methods:At the Department of Plastic and Reconstructive Surgery, University of Rome Tor Vergata, Italy, 11 patients underwent nasal alar reconstruction with chondrocyte micrografts gently pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…This construct, subcutaneously injected, resulted in a persistent cartilage tissue with appropriate morphology, adequate central nutritional perfusion without central necrosis or ossification, and further augmented nasal dorsum without obvious contraction and deformation. In addition, microscopic analysis of excisional fragments showed the persistence of healthy cartilage tissue with the formation of new capillaries penetrating into the cartilage as previously reported [29,30]. Here, we demonstrated that the Rigenera ® System is a useful method to isolate human chondrocytes when cells were injected with PRP in vivo in patients affected by nasal valve collapse and pinched nose deformity or cartilage defects.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…This construct, subcutaneously injected, resulted in a persistent cartilage tissue with appropriate morphology, adequate central nutritional perfusion without central necrosis or ossification, and further augmented nasal dorsum without obvious contraction and deformation. In addition, microscopic analysis of excisional fragments showed the persistence of healthy cartilage tissue with the formation of new capillaries penetrating into the cartilage as previously reported [29,30]. Here, we demonstrated that the Rigenera ® System is a useful method to isolate human chondrocytes when cells were injected with PRP in vivo in patients affected by nasal valve collapse and pinched nose deformity or cartilage defects.…”
Section: Resultssupporting
confidence: 84%
“…Chondrocytes obtained were suitable to form autologous micro-grafts, which could be used alone or in combination with Platelet Rich Plasma (PRP) as published [29,30], and as reported in a patient analyzed in this work, to obtain a biocomplex ready to be implantable in subjects in need of such intervention. PRP was prepared with the approval of the transfusional service from a small volume of blood.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of IGF-I and GDF-5 increased the thickness of engineered neocartilage 12-fold over the untreated control [106] in scaffold-free nasal neocartilage engineered from human septal chondrocytes. Other stimulation regimens which increase the content of desirable matrix components and mechanical properties include the use of TGF-β3, BMP-14, platelet rich plasma, and subcutaneous implantation [90,114,115,118,119]. Culture of multilayered P1 human septal chondrocytes in a rotating bioreactor increased construct cellularity and GAG per wet weight content by 200%, as well as bulk modulus by 32.5-fold and elastic modulus by 22-fold of engineered constructs compared to static culture controls [105].…”
Section: 3: Nasal Cartilage Tissue-engineeringmentioning
confidence: 99%
“…(Figure 3). It is likely that the simplicity and low morbidity of cartilage‐only nasal grafts has created the opportunity for immediate investigation in human patients 9,20‐22 . The promising results from these studies have enabled investigators to initiate movement toward larger‐scale trials 9 .…”
Section: Discussionmentioning
confidence: 99%